Program Pendampingan Tentang Hak Anak dalam Rangka Mencegah Perundungan (Bullying) dan Kekerasan Seksual di Lingkungan Sekolah: Pengabdian - Ekawestri Prajwalita Widiati; Zendy Wulan Ayu Widhi Prameswari; Amira Paripurna; Ajeng Anggraeni (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Understanding juvenile delinquency involves exploring the complex interactions between individual, family, social, and environmental factors that can influence the likelihood of youth engaging in unlawful activities. Given the critical developmental stage of adolescence, addressing and preventing juvenile delinquency is extremely important at this phase. The profile of Madiun Regency at East Java, as the "Village of Martial Artists" in Indonesia, is basically a good environment to foster young potentials, where they join martial arts from very young age. However, this potential must be managed with effective strategies to prevent juvenile delinquency. Effective strategies involve a combination of community-based programs, educational initiatives, counseling, and rehabilitation. The Community Service Program (PKM) at SMP Negeri 1 Jiwan Madiun focuses on strengthening inter-agency networks and developing learning models to prevent bullying and sexual violence. Through four key concepts, the program integrates child rights-based policy enforcement, emotional intelligence and conflict resolution training, and collaboration with universities and the police. Furthermore, a restorative justice approach is used as the primary method in addressing school conflicts to create empathetic and effective solutions.